2017
DOI: 10.1080/00268976.2017.1346832
|View full text |Cite
|
Sign up to set email alerts
|

Modelling magnetic anisotropy of single-chain magnets in |d/J| ≥ 1 regime

Abstract: Single molecule magnets (SMMs) with single-ion anisotropies d, comparable to exchange interactions J, between spins have recently been synthesized. In this paper, we provide theoretical insights into the magnetism of such systems. We study spin chains with site spins, s = 1, 3/2 and 2 and on-site anisotropy d comparable to the exchange constants between the spins. We find that large d leads to crossing of the states with different MS values in the same spin manifold of the d = 0 limit. For very large d's we al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, large quantum tunneling of magnetization leads to small hysteresis loops. In our previous studies [30], we have shown that large magnetic anisotropy of building blocks leads to breaking the spin symmetry. In this event associating a parent spin state to define the D M and E M parameters of a cluster is not possible due to intrusion of states from different parent spins within the given spin manifold.…”
Section: Introductionmentioning
confidence: 92%
“…However, large quantum tunneling of magnetization leads to small hysteresis loops. In our previous studies [30], we have shown that large magnetic anisotropy of building blocks leads to breaking the spin symmetry. In this event associating a parent spin state to define the D M and E M parameters of a cluster is not possible due to intrusion of states from different parent spins within the given spin manifold.…”
Section: Introductionmentioning
confidence: 92%
“…The main focus of molecular magnetism has, therefore, been on raising the blocking temperature for magnetization relaxation by increasing the magnetic anisotropy barrier. Several earlier studies focused on analyzing the effect of on-site anisotropy as well as exchange anisotropy on the magnetic anisotropy barrier [8][9][10][11]. Single-chain magnets (SCMs) were subsequently synthesized, with the expectation that they will have a higher blocking temperature [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the Raman process, the intermediate vibrational state is a virtual state and is hence a higher-order quantum process. The inverse relaxation time in a one-phonon or direct process is linearly dependent on temperature, while that in a Raman process depends on the ninth power of temperature (T 9 ), and the Orbach process has an exponential dependence on temperature. Spin-spin relaxation mechanisms consider both the hyperfine and dipolar interaction terms.…”
Section: Introductionmentioning
confidence: 99%
“…The SMMs are characterized by exchange interactions between magnetic centers which are often frustrated 21 . There have been many theoretical studies in SMMs and SCMs and the role of on-site anisotropies and exchange anisotropies in determining the overall magnetic anisotropy of the SMMs and SCMs 22,23 . The overall magnetic anisotropy is expected to control the blocking temperature T B of the system.…”
Section: Introductionmentioning
confidence: 99%